Feminist Advocacy, Family Law and Violence against Women
1 online resource (286 pages)
Keywords: Around the world, discriminatory legislation prevents women from accessing their human rights. It can affect almost every aspect of a woman's life, including the right to choose a partner, inherit property, hold a job, and obtain child custody. Often referred to as family law, these laws have contributed to discrimination and to the justification of gender-based violence globally. This book demonstrates how women across the world are contributing to legal reform, helping to shape non-discriminatory policies and to counter current legal and social justifications for gender-based violence. The book takes case studies from Brazil, India, Iran, Lebanon, Nigeria, Palestine, Senegal, and Turkey, using them to demosntrate in each case the varied history of family law and the wide variety of issues impacting women’s equality in legislation. Interviews with prominent women's rights activists in three additional countries are also included, giving personal accounts of the successes and failures of past reform efforts. Overall, the book provides a complex global picture of current trends and strategies in the fight for a more egalitarian society.These findings come at a critical moment for change. Across the globe, family law issues are contentious. We are simultaneously witnessing an increased demand for women’s equality and the resurgence of fundamentalist forces that impede reform,invoking rules rooted in tradition, culture, and interpretations of religious texts. The outcome of these disputes has enormousramifications for women’s roles in the family and society. This book tackles these complexities head on, and will interest activists, practitioners, students, and scholars working on women's rights and gender-based violence.